No. VIII: Fidelio - Kolb, Alois, 1875-1942 (artist):::Creator:::::::::::: (Austria; Karl König; Vienna, 2021)
Engraving depicting the dungeon scene in the opera Fidelio, op. 72, with a female descending stairs leading to a man sitting on a stone, head in hand. No. VIII from Kolb's cycle of ten engravings.